Structural evidence for distinct IgG subclass-specific Fc receptors on mouse peritoneal macrophages - Lane, BC (The Rockefeller University Press, 1980)
Membrane proteins which selectively bind to the Fc portion of IgG were identified in the Nonidet P-40 extracts of radiolabeled thioglycollate- elicited mouse peritoneal macrophages. Affinity columns of various IgG preparations coupled to Sepharose 4B were used to absorb the Fc-binding proteins. Analysis of the acetic acid or sodium dodecyl sulfate (SDS) eluates from aggregated human IgG or antigen-complexed rabbit IgG columns revealed two Fc(gamma)/-specific proteins with apparent 67,000 and 52,000 mol wt. These proteins were not detected in acid or SDS eluates from F(ab’)(2) columns or in eluates from IgG column, over which were passed lysates of Fc receptor-negative cells. With the use of affinity columns that contained aggregated mouse myeloma proteins of different IgG subclasses, we found that the 67,000-dahon protein selectively binds to IgG2a, whereas the 52,000-dalton protein binds to IgG1 and IgG2b. Neither protein was found in SDS eluates from IgG3 columns. Trypsin treatment of the macrophages before detergent lysis removed the 67,000-dalton protein, although it leaves intact the 52,000-dalton protein. These results provide structural confirmation for the existence of separate Fc receptors on mouse macrophages and indicate that the two Fc-binding proteins identified in this study represent all or part of the trypsin- sensitive Fc receptor which binds IgG2a and the trypsin-resistant Fc receptor which binds IgG2b and IgG1.